Microbial phytase supplementation for improving availability of plant phosphorus in the diet of the growing pigs - Näsi, Matti (Agricultural and Food Science, 1990)
The effect of a phytase supplement produced by Aspergillus niger on phytinphosphorus availability for pigs on phytase deficient maize-soybean meal diets was measured in two digestibility and balance experiments involving twelve growing pigs. Apparent digestibility of P in diets without inorganic-P supplementation or with low addition (0.18 of total P) was significantly lower than in the control diets (0.16 and 0.23 vs. 0.42; P<0.01), respectively. Phytase supplementation improved P digestibility (P<0.01) such that plant-P digestibility (0.40 and 0.28) rose to the same level as the control diet. P retention was also increased significantly by phytase supplementation. Calcium digestibility and retention were higher in phytase treated diets. Due to its effect on phytate-P availability, phytase treatment of feedstuffs allows a greater proportion on the pig’s P requirement to be met by P of plant origin.